2022
DOI: 10.1093/nar/gkac384
|View full text |Cite
|
Sign up to set email alerts
|

Cancer driver drug interaction explorer

Abstract: Cancer is a heterogeneous disease characterized by unregulated cell growth and promoted by mutations in cancer driver genes some of which encode suitable drug targets. Since the distinct set of cancer driver genes can vary between and within cancer types, evidence-based selection of drugs is crucial for targeted therapy following the precision medicine paradigm. However, many putative cancer driver genes can not be targeted directly, suggesting an indirect approach that considers alternative functionally relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A plethora of computational methods have been developed for drug target identification and drug repurposing [46]. Many of these methods already use networks as input [4749] and embrace concepts of network pharmacology [50]. Typically, such methods extract disease modules after connecting patient- or disease-specific seed genes.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of computational methods have been developed for drug target identification and drug repurposing [46]. Many of these methods already use networks as input [4749] and embrace concepts of network pharmacology [50]. Typically, such methods extract disease modules after connecting patient- or disease-specific seed genes.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5 , in the CADDIE database ( 59 ), we found that the downstream genes STAT3, AKT1, IGF1R, and BCAT1 of LINC00324 have multiple targeted drugs. They include STAT3-targeted drugs (Digoxin, Acitretin, Ouabain, Digitoxin, and Niclosamide), AKT1-targeted drugs (Gefitinib, Sorafenib, Erlotinib, Imatinib, and Risperidone), IGF1R-targeted drugs (Insulin human, Sorafenib, Masoprocol, Erlotinib, and Gefitinib), and BCAT1-targeted drugs (Pyridoxal phosphate, Glutamic Acid, L-Leucine, L-Valine, and Isoleucine).…”
Section: Clinical Value Of Linc00324 In Cancermentioning
confidence: 94%
“…miR-1294 and cancer therapy As shown in Fig. 3, we found that currently listed drugs can target 6 downstream genes of miR-1294 via the CADDIE website (https://exbio.wzw.tum.de/caddie/drug-lookup) [49]. These drugs are Palifermin, Heparin, Regorafenib, Ponatinib, and Lenvatinib targeting FGFR1, R788 (Fostamatinib) targeting PLK1 and PIM1, C225 (Cetuximab), LIDO (Lidocaine), (ZD1839) Gefitinib targeting EGFR, Erlotinib, and Lapatinib; Insulin and Mecasermin targeting IGF1R, and ATO and RESV (Resveratrol) targeting AKT1.…”
Section: The Relationship Between Mir-1294 and Clinicopathological Ch...mentioning
confidence: 95%